Cytokine Networks and the Clinical Outcome of American Teg-Umentary Leishmaniasis: Unveiling Targets for Alternative Therapeutic Interventions - Carolina Cattoni Koh; Kenneth J. Gollob; Walderez O. Dutra (Pathogens, 2025)
American Tegumentary Leishmaniasis (ATL), caused by parasites of the genus Leishmania, presents a significant global health challenge, especially in Brazil, where cutaneous and mucosal forms are highly prevalent. Cutaneous Leishmaniasis (CL) typically results in single lesions, while mucosal Leishmaniasis (ML) leads to destructive mucosal lesions with a worse prognosis. The immune response, regulated by cytokines, plays a crucial role in disease progression and resolution. In CL, a balance between pro-inflammatory and anti-inflammatory cytokines is associated with lesion resolution, whereas in ML, an exaggerated inflammatory response worsens tissue damage. Thus, understanding cytokine regulation is essential for unveiling disease pathology and developing effective immunotherapeutic strategies. Here we discuss gene polymorphisms and epigenetic modifications that affect cytokine expression, influencing disease susceptibility and severity, as well as immunotherapeutic approaches that involve cytokine function in Leishmaniasis. In addition, we examine advancements in drug discovery, utilizing in silico methods and targeted drug delivery systems, providing potential avenues for better therapeutic interventions. Continuous research into immune responses and cytokine production and function is critical for identifying novel therapeutic targets and optimizing patient care for ATL.